2018
DOI: 10.1080/1354750x.2018.1427795
|View full text |Cite
|
Sign up to set email alerts
|

Down-expression of P2RX2, KCNQ5, ERBB3 and SOCS3 through DNA hypermethylation in elderly women with presbycusis

Abstract: Down-expressed genes associated with DNA hypermethylation could be used as biomarkers for understanding complex pathogenic mechanisms underlying presbycusis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In addition, reduced expression of P2RX2, KCNQ5, ERBB3, and SOCS3 genes through DNA hypermethylation in elderly women was associated with presbycusis [48]. More recently, Bouzid et al demonstrated that hypermethylation of CpG site in the cadherin-23 (CDH23) gene is likely to be associated with presbycusis in elderly women [48]. These results implicate complex pathogenic mechanisms underlying ARHL.…”
Section: Dna Methylationmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, reduced expression of P2RX2, KCNQ5, ERBB3, and SOCS3 genes through DNA hypermethylation in elderly women was associated with presbycusis [48]. More recently, Bouzid et al demonstrated that hypermethylation of CpG site in the cadherin-23 (CDH23) gene is likely to be associated with presbycusis in elderly women [48]. These results implicate complex pathogenic mechanisms underlying ARHL.…”
Section: Dna Methylationmentioning
confidence: 95%
“…Furthermore, Xu et al [47] reported that hypermethylation of hearing-loss genes such as solute carrier family 26 member 4 (SLC26A4, DFNB4) and purinergic receptor P2X 2 (P2RX2, DFNA41) resulted in an increased risk for presbycusis in men. In addition, reduced expression of P2RX2, KCNQ5, ERBB3, and SOCS3 genes through DNA hypermethylation in elderly women was associated with presbycusis [48]. More recently, Bouzid et al demonstrated that hypermethylation of CpG site in the cadherin-23 (CDH23) gene is likely to be associated with presbycusis in elderly women [48].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Rare gain-or loss-of-function KCNQ5 gene variants (32) and KCNQ5 haploinsufficiency (33) cause severe intellectual disability and epileptic encephalopathy. KCNQ5 polymorphisms have also been associated with myopia (34), while KCNQ5 down-regulation is found in presbycusis (age-related hearing loss) (35). For most or all of these conditions, a KCNQ5-selective opener would be anticipated to have potential therapeutic activity.…”
Section: Significancementioning
confidence: 99%
“…Alterations in both human and mouse methylation patterns have been hypothesized to play a role in the development of ARHL. In humans, hypermethylation and consequent decreased expression of several genes, including P2RX2 , KCNQ5 , ERBB3 , and SOCS3 , were observed in elderly women with ARHL (Bouzid, Smeti, Roche et al, ). Additionally, hypermethylation of SLC26A4 and P2RX2 conferred increased risk of ARHL in men (Xu et al, ).…”
Section: Epigeneticsmentioning
confidence: 99%
“…In elderly women with ARHL, the degree of CDH23 CpG site methylation in peripheral blood samples demonstrated a positive correlation with ARHL. These findings create the opportunity to employ methylation patterns readily obtained from blood samples as biomarkers for ARHL (Bouzid, Smeti, Roche et al, ).…”
Section: Epigeneticsmentioning
confidence: 99%